2018
DOI: 10.1016/j.dhjo.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity levels in children with sensory problems: Cross-sectional analyses from the Millennium Cohort Study

Abstract: Children with visual problems affecting both eyes, but not one eye, are likely to have lower levels of physical activity. Strategies to promote physical activity in children with visual problems are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…Similar findings were found for the variable ‘recognition of friends across street’ and ‘reading ordinary newspaper’ 14. The present authors have also found similar associations in young people 15. These findings are of importance owing to a high prevalence of reduced eyesight.…”
Section: Introductionsupporting
confidence: 88%
“…Similar findings were found for the variable ‘recognition of friends across street’ and ‘reading ordinary newspaper’ 14. The present authors have also found similar associations in young people 15. These findings are of importance owing to a high prevalence of reduced eyesight.…”
Section: Introductionsupporting
confidence: 88%
“…We assumed a causal pathway for the association between visual impairment and mortality as depicted in Figure 1, based on previous studies [5,6,7,8,9,12,13,14,19,20,21,22], to assess the independent association by identifying potential confounders and mediators. In brief, we selected older age, systematic diseases and conditions (body mass index, waist circumference, systolic and diastolic blood pressure, serum levels of fasting glucose, creatinine, aspartate aminotransferase, alanine aminotransferase, and gamma glutamyltransferase, and history of stroke, heart disease, hypertension, type 2 diabetes, dyslipidemia, and other diseases including cancer), income, residing area, and lifestyle factors (smoking status and alcohol consumption) as potential confounders, which could affect both visual function and mortality and possibly bias the results.…”
Section: Methodsmentioning
confidence: 99%
“…After identifying the potential confounders, we adjusted them in further analyses. We did not adjust for physical activity in the main models because physical activity may mediate the association between visual function and mortality partially (Figure 1) [5,19,21] and the association between visual impairment and mortality could be underestimated when adjusting for physical activity. Detailed information on selected covariates is presented in the Supplementary Material.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, another study, with a sample of 6001 participants residing in the United States of America (USA), also suggests that visual impairment is associated with lower levels of physical activity [13]. Research has also found that children with low vision do less physical activity than those with good vision [14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%